Relação conjugal em situação de câncer em um dos cônjuges - Picheti, Jeovana Scopel (Universidade do Vale do Rio dos Sinos, 2012)
This thesis is composed by two papers: the first one is a bibliometric review, and the second is an empirical research. The paper about the bibliometric review evaluated researches published in English between 2001 and 2011 that approached communication in couples in which one spouse has cancer. This research resulted in fourteen papers that highlight how important it is for the couple to talk about subjects related to their marital relationship and the cancer experience. The empirical research deals with multiple case studies and aims at evaluating the marital relationship when a spouse has cancer. Four couples took part in this study, and they were selected by convenience from a hospital in a town in the Serra Gaúcha region, state of Rio Grande do Sul. Semi-structured interviews were conducted with the couples and with the spouses separately. The interviews were recorded in audio and then transcribed. The cases were analyzed both individually and as a couple. It was possible to identify three thematic axes: Characterization of the life cycle of the couple, Intimacy/Sexuality and Communication. The results pointed to the fact that the participant couples were in a transition point between a middle-aged and an elderly life; patients in palliative care, patients who had difficulties in the marital experience because of the fact they played the role of caregiver/patient more often than the role of husband/wife; and the reaffirmation of international research results about the fact that the couples do not talk about changes in sexuality, as well as about the feelings concerning the possibility of death. It is possible to observe the importance of the communication about perceptions and feelings in couples that are experiencing cancer and about the changes in conjugality, as well as about the feelings regarding the possibility of death.
Keywords: Câncer; Relacionamento conjugal; Comunicação; Mudanças na conjugalidade; Ciclo vital do casal; Cancer; Marital relationship; Communication; Changes in conjugality; Life cycle of the couple; ACCNPQ::Ciências Humanas::Psicologia